Collabtifacts: collaborative project artifacts management system using cloud computing technology / Muhammad Danial Nordin - Nordin, Muhammad Danial (2015)
Bachelor of Information Technology (Hons.) Information Systems Engineering (ISE) students are having problem in governing their project artifacts, especially in the 3 core courses (ITS470, ITS570, ITS670) project that is continuous for 3 consecutive semester, where the deliverables of one course is an input to another. This project is aim to create a project artifact management system using cloud computing for students to manage their project and lecturers to monitor the students project progress. The students are having problems in synchronizing their efforts. This project was named Collabtifacts, which combine the word collaborate and artifacts. The project was split into 5 phase: Project Planning, Literature Review, Requirement Gathering and Analysis, System Design and System Development. Cloud technologies were reviewed and compared and Google Drive was chosen for this project. The requirements for this project was gathered by interview and questionnaire of the students. It was analyzed using Event Decomposition and CRUD technique and it was documented in Software Requirement Specification. The system design and structures were made in UML modelling technique saved in a Software Development Document (SDD). When system was in Beta development phase, 2 group of ITS670 students were given a test usage of the system and give their feedback in a Post-Usage Evaluation Form. They believe it could solve their problems, but some are reluctant to trust a new system. The lecturers were not able to give their feedbacks as the researcher time was limited. There are still some future work need to be done to fully implement the system.